Metformin impairs mitochondrial function in skeletal muscle of both lean and diabetic rats in a dose-dependent manner. - Bart Wessels (Public Library of Science (PLoS), 2014)
Metformin is a widely prescribed drug for the treatment of type 2 diabetes. Previous studies have demonstrated in vitro that metformin specifically inhibits Complex I of the mitochondrial respiratory chain. This seems contraindicative since muscle mitochondrial dysfunction has been linked to the pathogenesis of type 2 diabetes. However, its significance for in vivo skeletal muscle mitochondrial function has yet to be elucidated. The aim of this study was to assess the effects of metformin on in vivo and ex vivo skeletal muscle mitochondrial function in a rat model of diabetes. Healthy (fa/+) and diabetic (fa/fa) Zucker diabetic fatty rats were treated by oral gavage with metformin dissolved in water (30, 100 or 300 mg/kg bodyweight/day) or water as a control for 2 weeks. After 2 weeks of treatment, muscle oxidative capacity was assessed in vivo using 31P magnetic resonance spectroscopy and ex vivo by measuring oxygen consumption in isolated mitochondria using high-resolution respirometry. Two weeks of treatment with metformin impaired in vivo muscle oxidative capacity in a dose-dependent manner, both in healthy and diabetic rats. Whereas a dosage of 30 mg/kg/day had no significant effect, in vivo oxidative capacity was 21% and 48% lower after metformin treatment at 100 and 300 mg/kg/day, respectively, independent of genotype. High-resolution respirometry measurements demonstrated a similar dose-dependent effect of metformin on ex vivo mitochondrial function. In conclusion, metformin compromises in vivo and ex vivo muscle oxidative capacity in Zucker diabetic fatty rats in a dose-dependent manner.